Intraempreendedorismo no setor público: mapeando os comportamentos que impulsionam a gestão rumo à inovação - Tinoco, Alex Rocha (Brasil, 2025)
This study aimed to identify the behavioral characteristics of intrapreneurs in the public sector, since entrepreneurship in the public sector has been a tactic to bring citizens/users to public services, resulting in a modernization for the benefit of society, since by studying these behavioral characteristics, we can understand and put them into practice in a systemic way in public or private organizations. A qualitative approach was used to obtain the necessary results for this Systematic Literature Review (SLR). To obtain the results of the study, selection criteria were used, thus obtaining a series of behavioral characteristics aimed at the public sector. According to the studies analyzed, we identified in the classification of personal attributes (intrinsic) with a higher frequency of intrapreneurial behavioral characteristics mentioned. Intrapreneurs in the public sector are important for the development of public organizations for internal and external changes through the improvement of public services, through the generation of public value. The SLR used the PRISMA method. As a result of the survey, 456 were found and after applying the criteria, only 14 remained, which shows that studies focused on intrapreneurship in the public sector are still scarce.